Institutional Reform in Transition Economies : How Far Have they Come - Weder, Beatrice (Washington, D.C. : International Monetary Fund, 2001)
This paper examines how institutional conditions in transition economies compare with those in the rest of the world using various indicators of governance. The focus is on the countries in Central and Eastern Europe and the former Soviet Union but, when possible, transition countries, in Asia and Africa are also considered. The main findings are that transition economies, as a group, are no longer distinguishable from other economies, but at the same time, there are large differences in institutional performance within the group of transition economies. A formal cluster analysis is conducted in order to map transition economies into homogeneous groupings of countries. The results of this analysis highlight that transition economies are found at all clusters (from best to worst institutional performers) and also that a group of five countries, all of which are EU accession countries, appear to have 'graduated': when taking into account their level of income, their institutional conditions are no longer distinguishable from those in the most advanced industrialized countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Economy; Institutions; Transition Economy; Transition; WP; Czech Republic